2020
DOI: 10.1186/s40560-020-00443-6
|View full text |Cite
|
Sign up to set email alerts
|

Spinal cord autoregulation using near-infrared spectroscopy under normal, hypovolemic, and post-fluid resuscitation conditions in a swine model: a comparison with cerebral autoregulation

Abstract: Background: Few studies have investigated spinal cord autoregulation using near-infrared spectroscopy (NIRS). Here, we assessed spinal cord autoregulation under normal, hypovolemic, and post-fluid resuscitation conditions compared with cerebral autoregulation. Methods: Ten pigs (36.1 ± 1.1 kg) were anesthetized with 2.5% isoflurane, before phenylephrine administration at 0.5, 1, 2, and 5 μg kg −1 min −1 in a stepwise fashion at 10-min intervals (baseline), followed by similar administration of sodium nitroprus… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
8
1

Year Published

2020
2020
2025
2025

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 38 publications
(53 reference statements)
1
8
1
Order By: Relevance
“…In the liver, the TOI was pressure dependent over a wide MAP range, whereas, in the tongue, it was independent of blood pressure over a wide MAP range. These findings were consistent with those of our previous reports (11–13), indicating that the brain, tongue (muscle), and kidney are well autoregulated, whereas liver autoregulation is weak.…”
Section: Discussionsupporting
confidence: 93%
“…In the liver, the TOI was pressure dependent over a wide MAP range, whereas, in the tongue, it was independent of blood pressure over a wide MAP range. These findings were consistent with those of our previous reports (11–13), indicating that the brain, tongue (muscle), and kidney are well autoregulated, whereas liver autoregulation is weak.…”
Section: Discussionsupporting
confidence: 93%
“…In previous animal experiments, we have also observed that noradrenaline administration caused both SCBF and SCPP to increase in extensive SA clamping and non-clamping models [ 9 ]. In an experimental study by Kurita et al using near-infrared spectroscopy as a method of evaluating spinal cord circulation in order to assess the balance of oxygen supply and demand in the spinal cord, the use of an α-adrenoreceptor agonist was seen to increase O 2 delivery to the spinal cord [ 20 ]. Noradrenaline has thus been experimentally demonstrated to improve spinal cord circulation from the perspectives of both SCBF and O 2 delivery.…”
Section: Discussionmentioning
confidence: 99%
“…Depending on several vascular and metabolic factors, a safe pressure level does not always ensure an adequate flow. Indeed, in animal models, spinal cord autoregulation is less robust than cerebral autoregulation and more pressure-dependent, hence SC is more sensitive to hypotension 16 . Noteworthy, Vanpeteghem et al, found different effects of phenylephrine and ephedrine on cerebral oxygen saturation and paraspinal oxygen saturation.…”
Section: Discussionmentioning
confidence: 99%